A case report on severe atypical bullous erysipelas induced by Escherichia coli in an immunosuppressed individual - Zhang, Xuemei; Yuan, Rui; Chen, Jun (Frontiers in Immunology, 2025)
A 60-year-old female patient with a prolonged history of immunosuppression due to a 20-year condition of rheumatoid arthritis, managed with long-term glucocorticoids and immunosuppressants, developed atypical erysipelas caused by Escherichia coli, complicated by septic shock and multiple organ dysfunction. Clinically, she presented with abrupt onset of redness, swelling, warmth, and pain in the left lower limb, which rapidly evolved into multiple vesicles and blood-filled blisters (2–3 cm in diameter) with rupture and exudation within 24 hours, subsequently progressing to septic shock and multiple organ dysfunction. Both vesicle fluid culture and next-generation sequencing (NGS) of blood samples confirmed the presence of Escherichia coli. Following the initial ineffective treatment with cefuroxime, the regimen was escalated to meropenem in combination with teicoplanin. Upon confirmation of the pathogenic microorganism, the treatment was de-escalated to piperacillin/tazobactam within 24 hours, supplemented by comprehensive wound management (iodophor wet dressing, lithospermum oil application, and red light therapy) and organ support therapy. After 10 days of intensive treatment, the patient recovered, and the wound healed completely after 4 months of care. This case underscores three critical warnings: 1) the pathogen spectrum of erysipelas in immunosuppressed hosts shows a significant shift, necessitating vigilance against the possibility of Gram-negative bacterial infections, such as Escherichia coli; 2) atypical bullous skin lesions can serve as an early indicator of severe infection, with a rapid clinical course progressing to shock within 24 hours; 3) a tiered anti-infective strategy is paramount – initially broad-spectrum coverage for both Gram-negative and Gram-positive bacteria (e.g., anti-pseudomonal β-lactams plus glycopeptides), followed by de-escalation within 24 hours of pathogen identification. It is advisable to conduct early combined microbial culture and NGS testing for immunosuppressed patients presenting with skin infections, and to implement individualized broad-spectrum antibiotic regimens to enhance prognosis.